Urgensi Kompetensi Guru Dalam Implementasi Pendidikan Integratif - Alex Nanang (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2016)
Education is a strategic pattern to improve the quality of a nation.moreover, the future and progress of a nation can be measured by the qualityof education. Because through education, science transformation processcan continue from generation to generation. Even through from education,improvement of human resources can be maximized. One of the importantfactor that determines the success of an educational process is an educatoror teacher. In this context, the teacher as the frontline and components thathave a strategic role in the educational process. in the end, the execution oftheir duties, teachers are required to have competence in creating integrativeeducation. For that reason, this paper is expected to provide a basicexplanation of the importance of teacher’s competencies in order to creatthe integrative education.